Influence treatment time of lanthanum conversion coating on magnesium alloy - Nurul Farah Wahida Binti Mohd Sidik (School of Manufacturing Engineering, University Malaysia Perlis, 2010)
This final report consists of several key sections, which are: introduction, problem faced, method of solution, result, discussion and conclusion. Introduction of project described briefly about the material used that is magnesium alloy AZ91D.